- #1

- 1

- 0

**1. Homework Statement**

(a; b) is in terms of D = ( 1,1 ; 1 -1) and (c; d) is in terms of Dx = ( -1,1 ; 0,2), then we need to find a matrix such that

(c;d) = (?, ?; ?, ?)* (a; b).

**2. Homework Equations**

y = Ax >> linear transformation

**3. The Attempt at a Solution**

I know the answer is [1, -3; 1, -1}...but all I can come up with is that

a(1;1) + b(1;-1) = c(-1;0) + d(1;2)

**1. Homework Statement**

**2. Homework Equations**

**3. The Attempt at a Solution**

**1. Homework Statement**

**2. Homework Equations**

**3. The Attempt at a Solution**